Noise level in the intensive care unit for adults: measurement, international standards and health implications - Garrido Galindo, Angélica Patricia; Camargo Caicedo, Yiniva; Vélez Pereira, Andrés M. (Universidad y Salud, 2015)
Objective: To assess the continuous equivalent noise level in an intensive care unit for adults that belongs to a hospital in the city of Santa Marta using the levels suggested by international standards. Materials and methods: A continuous sampling was done during 20 days where the data was recorded every minute by using a sound level meter type I in a central axis of the intensive care unit for adults in the hospital; the recorded data corresponded to the maximum, minimum values and the equivalent continuous level of noise on frequency weighting A and the Fast time weighting filter. Results: It was reported that the equivalent continuous noise level varied between 49-71 dBA with a maximum value of 91, 19 dBA and a minimum of 46, 65 dBA. The variance analysis infers that the mean value of noise varies according to the time of day. Conclusions: The level of equivalent continuous noise presented in the intensive care unit for adults is consistent with other similar studies; however, the displayed values exceed the international standards of noise suggested, which generates a concern about the risks of exposure for the patients as well as for the medical staff of the unit.